Informativeness of anamnestic data in children with seasonal symptoms of mold allergy - O. D. Kuznietsova; S. M. Nedelska (Zaporožskij Medicinskij Žurnal)
Aim. The results of clinical, anamnestic study of 154 children with seasonal symptoms of allergic rhinitis and/or bronchial asthma are declared in this article.